Interpersonal Communication at the Internal Group Level. (December 2013) - Rippa, Bella; Rippa, Ben; Moss, Eric
We all carry within ourselves unconscious images of significant figures from our past, which affect the way we relate to particular figures in the present. When considering group analysis, we see that each group member unconsciously brings to the therapy group his/her entire collection of inner significant objects, which may be individual objects and, as we will see in this article, may also be group objects. These may then be unconsciously projected onto individual members, the conductor and/or the group-as-a-whole and can affect their real behaviour in the group in positive and negative ways. The conductor's task is to help analyse these multiple transferences and projections in order to facilitate change.